Electrical characterization of ZnO/organic semiconductor diode - Caglar, Y.; Yakuphanoğlu, Fahrettin; Ilican, S.; Caglar, M. (Natl Inst Optoelectronics, 2008)
The electrical characterization of IZO/FSS/Al diode has been investigated current-voltage method. The ideality factor of the diode was found to be 2.84, which confirm that the IZO/FSS/Al device indicates a non-ideal I-V behaviour. The effect of series resistance was evaluated using a method developed by Cheung. The R-s and n values were determined from the dV/dln(I)-I plot and were found to be 8.00 k Omega and 2.84, respectively. The barrier height and R. values were calculated from H(I)-I plot and were found to be 0.86 eV and 7.83 k Omega At higher voltages, I-V characteristics of the diode are affected by the electrical properties. This suggests that at higher voltages, the current flow in the diode is controlled by the space limited current mechanism.
Keywords: Inorganic/organic semiconductor diode; Series resistance